2018
DOI: 10.1371/journal.pone.0203963
|View full text |Cite
|
Sign up to set email alerts
|

Association between the detection of alcohol, illicit drugs and/or psychotropic medications/opioids in patients admitted due to trauma and trauma recidivism: A cohort study

Abstract: ObjectiveTo quantify the association between the presence and type of drug detected and trauma recidivism in a cohort of patients admitted due to trauma.MethodA cohort study was conducted based on data from a project where the presence of alcohol and other drugs (cannabis, cocaine, amphetamines, methamphetamines, tricyclic antidepressants, barbiturates, opiates and benzodiazepines) was analysed in 1,187 patients aged 16 to 70 years admitted due to trauma. The patients were followed for a period of between 10 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…In short, although the literature has highlighted the relationship between the consumption of psychotropic medications and trauma, there is a lack of evidence on the impact that the consequences of the consumption of benzodiazepines, opioids and tricyclic antidepressants (osteoporosis, increased BMI) or other variables independent of the consumption of psychotropic medications (age, gender, cognitive decline, sensory conditions, diabetes, hypertension) may have on this relationship. Additionally, studies that have explored the prevalence of the consumption of benzodiazepines, opioids and tricyclic antidepressants and other substances in trauma patients find a high percentage of falls associated with people who consume these substances [24,25] but do not determine the effect size of the association between these factors or the role that other variables could play in the association. Therefore, the objective of the present study was to determine, in patients who have suffered trauma, the effect size of the association between psychotropic medication consumption and falls by studying the weights that the mediating and confounding variables may have in this association.…”
Section: Introductionmentioning
confidence: 99%
“…In short, although the literature has highlighted the relationship between the consumption of psychotropic medications and trauma, there is a lack of evidence on the impact that the consequences of the consumption of benzodiazepines, opioids and tricyclic antidepressants (osteoporosis, increased BMI) or other variables independent of the consumption of psychotropic medications (age, gender, cognitive decline, sensory conditions, diabetes, hypertension) may have on this relationship. Additionally, studies that have explored the prevalence of the consumption of benzodiazepines, opioids and tricyclic antidepressants and other substances in trauma patients find a high percentage of falls associated with people who consume these substances [24,25] but do not determine the effect size of the association between these factors or the role that other variables could play in the association. Therefore, the objective of the present study was to determine, in patients who have suffered trauma, the effect size of the association between psychotropic medication consumption and falls by studying the weights that the mediating and confounding variables may have in this association.…”
Section: Introductionmentioning
confidence: 99%
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two independent cohorts were reported on across the 29 records. Multiple papers reported findings from the Trondheim traumatic brain injury (TBI) (n=2),29 46 TRACK-TBI (n=2)51 52 and MOTIVA (n=2) studies 33 34. Additionally, several papers examined overlapping datasets, including two studies each from the National Trauma Data Bank in the USA,27 44 the Oslo University Hospital Emergency Department,25 30 the R Adams Cowley Shock Trauma Centre24 48 and a trauma centre in Taiwan 32 45.…”
Section: Resultsmentioning
confidence: 99%
“…There is a well-established association between drugs/alcohol and criminal behavior and violence. 13,14 Cordovilla-Guardia and colleagues in their review of emergency room presentations noted specific associations between violence-related injury and the use of marijuana or cocaine. 14 Our study identifies a clear relationship between interpersonal violence and injury with 67% of patients either admitting to being currently under the influence of drugs or their intercurrent use describing the mechanism of their injury to be assault.…”
Section: Discussionmentioning
confidence: 99%